Quantifying and mapping the evolution of a leader journal in the field of civil engineering - Tang, Ming; Liao, Huchang; Yepes, Víctor; Laurinavičius, Alfredas; Tupėnaitė, Laura (Journal of Civil Engineering and Management, 2021)
Automation in Construction is one of the leading international journals in construction and building dating back to 1992. This study aims to quantify and visualize the evolution of Automation in Construction publications using bibliometric methods. Our work has two parts: 1) publication and citation statistics in terms of annual distributions, citing sources, prolific countries/regions and institutes, and highly cited papers, 2) network and science mapping analyses in terms of co-authorship network, co-citation network and thematic evolution. Two bibliometric software, VOSviewer and SciMAT, are used to help us carry out the analyses. The results suggest that Automation in Construction has obtained increasing influence and reputation from scientific community over the past decades. It is expected that our study has guiding significance for editors and readers of this journal through providing key insights about the evolution over time.